Patterns of Hemispheric Compromise in Primary Progressive Apraxia of Speech: From Clinical Profiling to Differential Diagnosis - Garcia-Serrano, A (John Wiley and Sons Inc, 2023)
In this issue of European Journal of Neurology, Robinson et al. present a novel study on primary progressive apraxia of speech. The authors describe different clinicopathological profiles in patients with left-dominant, right-dominant, and bilateral atrophy of the supplementary motor area and lateral premotor cortex. This commentary discusses the importance of this evidence for understanding individual differences among these patients, distinguishing them from those with nonfluent variant primary progressive aphasia, and analyzing the relations between motor speech deficits and underlying pathology. © 2023 European Academy of Neurology.